2018
DOI: 10.5152/tjg.2017.17349
|View full text |Cite
|
Sign up to set email alerts
|

A proposed role for diffusible signal factors in the biofilm formation and morphological transformation of Helicobacter pylori

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…At the cellular level, the best-described morphological change in Hp associated with biofilm in vivo is coccoid transformation (Carron et al, 2006; Coticchia et al, 2006; Cellini et al, 2008). Coccoid transformation is considered a common feature of Gram-negative rod bacteria under conditions of stress (Andersen and Rasmussen, 2009; van Teeseling et al, 2017; Krzyzek and Gosciniak, 2018). In vitro , coccoid forms of Hp can be induced by prolonged culture or use of suboptimal levels of antibiotics (Krzyzek and Gosciniak, 2018; Poursina et al, 2018).…”
Section: Functional and Morphological Changes Associated With Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, the best-described morphological change in Hp associated with biofilm in vivo is coccoid transformation (Carron et al, 2006; Coticchia et al, 2006; Cellini et al, 2008). Coccoid transformation is considered a common feature of Gram-negative rod bacteria under conditions of stress (Andersen and Rasmussen, 2009; van Teeseling et al, 2017; Krzyzek and Gosciniak, 2018). In vitro , coccoid forms of Hp can be induced by prolonged culture or use of suboptimal levels of antibiotics (Krzyzek and Gosciniak, 2018; Poursina et al, 2018).…”
Section: Functional and Morphological Changes Associated With Biofilmmentioning
confidence: 99%
“…Coccoid transformation is considered a common feature of Gram-negative rod bacteria under conditions of stress (Andersen and Rasmussen, 2009; van Teeseling et al, 2017; Krzyzek and Gosciniak, 2018). In vitro , coccoid forms of Hp can be induced by prolonged culture or use of suboptimal levels of antibiotics (Krzyzek and Gosciniak, 2018; Poursina et al, 2018). The Hp coccoid forms have been defined as viable but non-culturable (VBNC), thus undetectable by conventional cultures, and are known to have an increased capacity to aggregate into monomicrobial clusters embedded in thick EPS (Cellini et al, 2008; Cellini, 2014; Krzyzek and Gosciniak, 2018).…”
Section: Functional and Morphological Changes Associated With Biofilmmentioning
confidence: 99%
“…Morphological plasticity as a mechanism enabling the adaptation of microbes to changing environmental conditions may explain the high heterogeneity of the H. pylori population [ 13 ] ( Figure 1 ). Classical classification of H. pylori morphological forms includes the division into: live, culturable spiral forms – related to the process of host colonisation, and live, non-culturable coccoid forms – associated with the viable but non-culturable (VBNC) process and the survival of this bacterium under unfavourable conditions [ 14 ]. In addition, the existence of rod-shaped and filamentous forms of H. pylori is also noted [ 7 , 8 , 15 , 16 ].…”
Section: Morphological Forms Of Helicobacter Pylorimentioning
confidence: 99%
“…9,23 Streptococci are a source of SDSF (Streptococcus diffusible signal factors), which may be involved in the morphological transformation of H. pylori into coccoid forms. 48 In an experiment, Khosravi et al determined the effect of H. pylori and S. mitis co-culture on the gene expression of both bacteria. 47 It was observed that streptococci expressed genes encoding phosphoglycerate kinase (PGK) only when co-existing with H. pylori.…”
Section: Interactions Of Oral H Pylori With Microbial Fl Oramentioning
confidence: 99%